Diabetes e Depressão numa amostra de idosos hospitalizados: comparação sociodemográfica e clínica entre doentes com e sem diabetes - Susana Raquel Barbosa Teixeira (2021)
Introduction: Diabetes Mellitus is a chronic disease with the prevalence increasing worldwide, namely in elderly, being one of the main causes of mortality and morbidity. Depression is often associated with this pathology, worsening its prognosis. Objectives: This study aimed to assess depression in these patients, comparing sociodemographic and clinically two samples of elderly patients with and without diabetes. Material and Methods: The study included elderly patients hospitalized into a ward of the Internal Medicine Service of a University Hospital, evaluated with the: Hospital Anxiety and Depression Scale-Depression Subscale, Barden's Scale, Morse's Scale, Charlson's Comorbidity Index and Mini-Nutritional Assessement. Mann-Whitney and Chi-square statistical tests were used to compare patients with and without diabetes. Results: The sample included 33 hospitalized patients (14 diabetic and 19 non-diabetic). In the diabetics, there was a higher percentage of arterial hypertension (100.0% vs 68.4%, p = 0.027), dyslipidemia (100.0% vs 57.9%, p = 0.010), higher number of medical illnesses (median 7 vs 4; p = 0.002), daily medication (median 9 vs 4; p <0.001) and a higher score in the Charlson Comorbidity Index (median 4 vs 1; p = 0.001). There was more diabetic patients with depression, but this difference was not statistically significant. Conclusion: Diabetic patients had more arterial hypertension, dyslipidemia and prescription medicines, which is in line with other previous studies. This study appears as a contribution to the characterization of hospitalized diabetic elderly, as well as to the definition of intervention plans based on the specific needs and risks of this population.